Anesthesiologists’ Preferences regarding Visitor Presence during Placement of Neuraxial Labor Analgesia - Sangeeta Kumaraswami; Suryanarayana Pothula; Mario Anthony Inchiosa; Keshar Paul Kubal; Micah Alexander Burns (Anesthesiology Research and Practice)
Introduction. Neuraxial labor analgesia has become an integral part of modern obstetric anesthetic practice. Presence of a familiar person during its placement may be beneficial to the patient. A survey was sent to anesthesiologists practicing obstetric anesthesia in the USA to determine their views. Methods. The survey queried the following: existence of a written policy; would they allow a visitor; visitor’s view, sitting or standing; reasons to allow or not allow a visitor; and influence by other staff on the decision. The responses were analyzed using multiple chi-square analyses. Results. Most practitioners supported allowing a visitor during placement. Reduction of patient anxiety and fulfillment of patient request were the major reasons for allowing a visitor. Sitting position and no view of the workspace were preferred. Visitor interference and safety were cited as the major reasons for precluding a visitor. Nonanesthesia providers rarely influenced the decision. Epidural analgesia was the preferred technique. Essentially no bias was found in the responses; there was statistical uniformity regardless of procedures done per week, years in practice, professional certification, geographic region (rural, urban, or suburban), or academic, private, or government responders. Conclusion. The practice of visitor presence during the placement of neuraxial labor analgesia is gaining acceptance.